Re-evaluation of Yam Mosaic Virus (YMV) detection methods - Eni, A.; Hughes, J.; Asiedu, Robert; Rey, M. (International Digital Organization for Scientific Information (IDOSI), 2012)
Accurate and timely detection is vital for mitigation of tuber yield losses resulting from yam mosaic virus (YMV) infection on yam, a major food security crop in West Africa. The observation, from our previous studies, that the triple antibody sandwich enzyme-linked immunosorbent assay (TAS-ELISA), the most commonly used detection method for YMV, detected the virus in significantly less leaf samples than immunocapture reverse transcription polymerase chain reaction (IC-RT-PCR) necessitated a re-evaluation of YMV detection methods. In the present study, eighteen previously tested YMV positive leaf samples from Benin and Ghana were re-tested using TAS-ELISA, Protein A-sandwich (PAS) ELISA and IC-RT-PCR. Three sap dilutions, 1/10, 1/50 and 1/100, were tested for each sample. Both at 1/10 and 1/50 dilutions, PAS-ELISA and IC-RT-PCR detected YMV in 11 (61.1%) and 12 (66.7%) of the leaves respectively. Virus detection by PAS-ELISA reduced to 50% at 1/100 sap dilution and increased to 77.8% in IC-RT-PCR. YMV detection by TAS-ELISA varied between 38.9% and 16.7% at 1/10 and 1/100 dilutions respectively. These results indicate a deficiency in the use of TAS-ELISA as a sole YMV certification method since the detecting monoclonal antibody used in this assay may be strain specific. The use of PAS-ELISA at a 1/10 sap dilution is suggested for YMV detection where the facilities for molecular detection are unavailable.